THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND COMPETENCY TOWARDS THE PRODUCTIVITY OF PUBLIC PRIMARY SCHOOL PRINCIPALS IN THE FIELD OF PRIMARY EDUCATION DEPARTMENT OF BATAM CITY: THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND COMPETENCY TOWARDS THE PRODUCTIVITY OF PUBLIC PRIMARY SCHOOL PRINCIPALS IN THE FIELD OF PRIMARY EDUCATION DEPARTMENT OF BATAM CITY - Ibadi, Allazi; Hikmahardya, Nurmaya; Husniah, Hudratil Yaumil; S, Eka Wahuni S; ardyatama, Ade khrisna; khoirunnisa, Istiqomah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This research aims to obtain information regarding the relationship between independent variables, namely; Transformational leadership (X1), organizational culture (X2), work motivation (X3), and Competency (X4) with the dependent variable being the work productivity of the Principal of the State Elementary School (Y) Primary School Development Sector of the Batam City Education Service, both individually and collectively. The population of this study was all employees of the Head of SDN for Primary School Development at the Batam City Education Department, totaling 145 people. In this study, there was no classification of differences between State Primary School Principals based on type or class status, both types of State Primary School Principals had the same treatment. Samples were taken using simple random sampling techniques. By using the Slovin formula, a sample of 59 people was obtained. The research results show a significant positive influence of transformational leadership (X1), organizational culture (X2), work motivation (X3), and Competency (X4) on the work productivity of State Elementary School Principals (Y) as indicated by the F valuecount amounting to 30,627. This value is much smaller than the F valuecount at the alpha significance level of 0.05, namely 2.95, or F = 30.627 < F0,05(4:57) = 2.54. The relationship pattern of the four variables is expressed by the multiple regression equation = -9,643 + 0,357X1 + 0,328X2 + 0,167X3 + 0.597X4. This means that the better the transformational leadership of the Principal of the State Primary School, the better the organizational culture in which the Principal of the State Primary School works, the higher the work motivation of the Principal of the State Primary School, and the higher the competency received by the Principal of the State Primary School, the higher the work productivity will be. Principal of the State Elementary School. Previously, based on validity and reliability tests, all instruments met the validity and reliability requirements. If calculated per variable, the variable that has the most influence is the organizational culture variable, which has a coefficient of determination of 54.1%. This means that organizational culture is the factor that most influences the work productivity of State Elementary School Principals.